Effects of far-red light on growth, endogenous hormones, antioxidant capacity and quality of Lettuce - Lili Meng; Jiangfeng Song; Degang Ni; Mohamad Anuar Kamaruddin (Food Production, Processing and Nutrition, 2024)
Abstract This study aimed to explore the effects of various intensities of far-red light on the growth performance, endogenous hormones, antioxidant indices, and overall quality of hydroponically cultivated lettuce. As the control treatment, a white LED emitting light at an intensity of 200 µmol/(m2·s) was utilized (referred to as CK with an R/FR ratio of 5.5), while two experimental treatments, FT1 (R/FR = 1.2) and FT2 (R/FR = 0.8), were established by adding different intensities of far-red light to the CK treatment. The results demonstrated that the application of far-red light, particularly in FT1, led to a significant increase in plant height, leaf area, and lettuce biomass, while simultaneously resulting in a notable reduction in leaf thickness. The content of indole-3-acetic acid (IAA) and abscisic acid (ABA) in response to far-red light treatments exhibited an initial increase followed by a subsequent decrease, with FT2 experiencing a significant decline. The gibberellin (GA3) content in FT2 reached its peak on the 35th day, showing a substantial increase of 60.09% compared to CK. Far-red treatments were found to enhance peroxidase (POD) and catalase (CAT) activities, while significantly reducing superoxide dismutase (SOD) activity. In comparison to CK, FT1 exhibited a remarkable 134.33% increase in anthocyanin content. Both FT1 and FT2 significantly boosted vitamin C levels while reducing nitrite content. Additionally, the application of far-red light treatment significantly increased the alcohol and ester content in lettuce leaves. This study establishes a theoretical foundation for enhancing the quality and flavor of lettuce using different far-red light treatments. Graphical Abstract